PEMBUATAN PC GAME ENDLESS RUN “ZOMBIE RUN” MENGGUNAKAN ARDUINO PRO MICRO DAN GY-521 SEBAGAI KONTROLER GYROSCOPE - Rei Malchiel; Tony Tony; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
“Zombie Run” is an endless running game that must played by two players on one computer or notebook and must be played using Arduino Pro Micro and GY-521 as controller. This game developed using Unity 3D game engine and controller developed using Arduino SDK. Player have to avoid as many obstacles to create highest score. Player can get uniquely exciting experience by tilting controller and pressing button in the controller to make character move. Testing has been done using blackbox method, alpha testing, and beta testing. The result show that this game have interesting concept by two players and gyroscope controller